2021
DOI: 10.1080/21655979.2021.1923381
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of N6-methyladenosine -related long non-coding RNAs and immune cell infiltration in hepatocellular carcinoma

Abstract: We aimed to illustrate the influence of N6-methyladenosine (m6A) long non-coding RNAs (lncRNAs) and immune cell infiltration in hepatocellular carcinoma (HCC). The relationship of lncRNAs and m6A was identified through gene expression analysis using PERL and R packages. The Kyoto Encyclopedia of Genes and Genomes gene expression enrichment analysis was performed via gene set enrichment analysis. Lasso regression was utilized to construct prognostic model. Differences in the tumor microenvironment and the immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Transcription and human configuration data were matched by Perl to obtain the precise mRNA gene expression data. The gene IDs were transformed into gene names by R4.1.0 [16]. In order to evaluate the difference of NRGs expression (DEGs) with statistical significance, FDR <0.05 and |log2FC|≥0.585 as a selection criteria.…”
Section: Annotation Of Genes Identification Of Nrgs and Its Mutation Ratesmentioning
confidence: 99%
“…Transcription and human configuration data were matched by Perl to obtain the precise mRNA gene expression data. The gene IDs were transformed into gene names by R4.1.0 [16]. In order to evaluate the difference of NRGs expression (DEGs) with statistical significance, FDR <0.05 and |log2FC|≥0.585 as a selection criteria.…”
Section: Annotation Of Genes Identification Of Nrgs and Its Mutation Ratesmentioning
confidence: 99%
“…Emerging evidence has demonstrated that m6A-related genes could be prognostic markers for predicting the survival time of patients [ 42 – 44 ]. In recent years, the role of m6A related lncRNAs has been recognized profoundly in HCC [ 45 , 46 ]. And studies in terms of prognosis of HCC patients were also accumulated.…”
Section: Resultsmentioning
confidence: 99%
“…As an instance, high expression level of LINC00958 which is mediated by m6A modification predicts poor overall survival of HCC patients independently [ 47 ]. Moreover, studies using a comprehensive informatics analysis based on data from TCGA database revealed that m6A methylated lncRNA was closely related to the prognosis of HCC [ 48 50 ]. However, more effective and specific prognostic biomarkers still needed.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we suggest that AL157392.3 may influence the development of AML through the glycolytic pathway. Moreover, AC145207.5 was only found to play a role in developing hepatocellular carcinoma, but not in AML ( Yu and Zhu, 2021 ; Zhou et al, 2021 ). The other six lncRNAs were rarely reported in cancers and further research should be conducted to reveal their potential role in AML development.…”
Section: Discussionmentioning
confidence: 98%